Fatal Mucormycosis and Aspergillosis in an Atypical Host: What Do We Know about Mixed Invasive Mold Infections?. (26th August 2020) - Tsikala-Vafea, Maria; Cao, Weibiao; Olszewski, Adam J.; Donahue, John E.; Farmakiotis, Dimitrios
Abstract : Mixed invasive mold infections (MIMIs) are considered rare. We present a case of fatal aspergillosis and mucormycosis in an elderly host with history of chronic lymphocytic leukemia (CLL) and potential mold exposures. Notably, he had no classic risk factors for IMI other than high-dose corticosteroids, which may be an important risk factor for (M)IMI, based on the current and previous reports. There is an urgent need for studies on the "net state of immunosuppression, " environmental exposure as risk factors for (M)IMIs, and noninvasive fungal diagnostics.